Kebijakan Politis Presiden Soeharto untuk Melanggengkan Kekuasaannya - Zaman, Jamrud Qomaruz (LoroNG: Media Pengkajian Sosial Budaya, 2019)
Indonesia is a democratic country that highly values the interests of its people. Therefore, authoritarian actions and absolute power by a leader do not show democratic values. Nevertheless, Indonesia has been recorded in its history to be led by an authoritarian and longstanding president, President Soekarno and President Suharto. Suharto was in power the longest between the two presidents, approximately 30 years (1968-1998). One of Suharto’s leadership hallmarks that distinguished him from other presidential leaderships was the formation of the ABRI Dwi Function doctrine. With the Dwi Function ABRI formation, Suharto intended to make it his prominent supporter in politics. The application of the dual function of ABRI has another motive to strengthen Suharto’s power during his presidency by making the party with the tremendous potential to overthrow him be subtly removed or made into an ally, namely the military. The policies to maintain his power, among others, were realized by giving the post of general to someone who was not capable, purging leftists (PKI), restricting the press, acting harshly on demonstrators, and attracting the sympathy of the Islamic group to be used. Negara Indonesia merupakan negara demokrasi yang sangat mengagungkan kepentingan rakyatnya. Oleh sebab itu tindakan otoriter dan berkuasa mutlak oleh seorang pemimpin sangat tidak menunjukkan nilai-nilai demokrasi. Walaupun demikian, Indonesia pernah tercatat dalam sejarahnya dipimpin oleh seorang presiden yang otoriter dan berkuasa lama, yakni presiden Soekarno dan presiden Soeharto. Diantara kedua presiden tersebut, Soeharto yang berkuasa paling lama dengan waktu lebih kurang 30 tahun (1968-1998). Salah satu ciri khas dari kepemimpinan Soeharto yang membedakannya dengan kepemimpinan presiden lainnya adalah pembentukan doktrin Dwi Fungsi ABRI. Dengan pembentukan Dwi Fungsi ABRI, Soeharto berniat menjadikannya sebagai pendukung utamanya dalam berpolitik. Penerapan Dwi Fungsi ABRI memiliki motif lain sehingga dapat memperkokoh kekuasaan Soeharto selama menjadi presiden dengan menjadikan pihak yang akan berpotensi besar melengserkannya dapat disingkirkan secara halus atau dijadikan sekutu, yaitu pihak militer. Adapun kebijakan-kebijakan sebagai upaya mempertahankan kekuasaanya tersebut antara lain diwujudkan dengan memberi jabatan jenderal kepada seseorang yang tidak cakap, membersihkan penganut paham kiri (PKI), membatasi pers, bertindak kasar terhadap para demonstran, dan menarik simpati golongan Islam untuk diperalat.